Precision medicine, predictive models of prognosis and quality of life in oncology - Silveira , Augusta; Guedes , Beatriz; Castro , Inês; Sequeira, Teresa; Guimarães , Maria Inês (Scientific Letters, 2024)
Background: Precision medicine or personalized medicine, is an approach to healthcare that emphasizes the customization of medical treatment and interventions to individual patients based on unique genetic, environmental, and lifestyle factors. Objective: To present Quality of Life results in Head and Neck Cancer patients. To discuss how patient reported outcomes can contribute to precision medicine. Methods: In this study, 380 head and neck cancer patients were evaluated. The published and validated Portuguese version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) was used. The QLQ-C30 (version 3) incorporates 5 functional scales (physical, role, cognitive, emotional, and social), 3 symptom scales (fatigue, pain, nausea and vomiting), the global health status/quality of life scale (QoL), and 6 single items to assess additional symptoms or problems (dyspnea, loss of appetite, insomnia, financial difficulties, constipation, and diarrhea). Results: The study showed that women have lower overall Quality of Life results. It also emphasizes the importance of early diagnosis, which often relates to stages with better prognosis and better Quality of Life outcomes. The study showed that tumor location has an impact on Quality of Life self-perception. Values of Health Related Quality of Life should be analyzed along with socio-demographic and clinical variables in order to better understand the epidemiology, pathogenesis, and prevention of these cancers favoring a precision medicine. Conclusions: Patient reported outcomes have been recognized as very useful in individual and multidisciplinary decisions. Routine provision of patient reported outcomes to oncologists positively affects the process of care in several dimensions such as oncologist–patient communication, awareness of patients’ problems and discussion of symptoms during consultations. Patient reported outcomes to support precision medicine providing the assessment to crucial data to provide effective, evidence-based supportive care, rehabilitation and symptom management.